Answer:
A3tx-A2b=cdx-2c
Step-by-step explanation:
Distribution
3 1/4 ounces = 3.25 Ounces.
3.25 x 5 = 16.25 ounces (16 1/4 ounces)
Answer:
8
Step-by-step explanation:
we can say that AD is congruent to DC
so your equation for x is: 4x - 1 = 2x
solve this to get x = 0.5
plug x into and equation and multiply you answer by 2 to find the hypotenuse of triangle ABC and DEF
4(0.5) - 1 = 1
hypotenuse: 1 x 2 = 2
since we know x is 0.5, plug this into 4x + 1 to find the length of the leg FE,
4(0.5) + 1 = 3
In the diagram, it shows that the legs of triangle are congruent
this means that FE, ED, BA, and BC are all congruent
since we know FE is 3, we know that all the other sides are 3 as well
this means that the perimeter of the triangle is: leg + leg + hypotenuse
so 3 + 3 + 2
the perimeter is 8
The person that is not living within their means is Ella who has maxed out all three of her credit cards but pays the minimum balance each month.
<h3>What does it mean when a person is living above their means?</h3>
If a person is living above their means, the person is spending more money than they have. A person living above their means would most likely borrow in order to afford their lifestyle. A person living above their means would have no amount of savings.
To learn more about credit cards, please check: brainly.com/question/14716152
<h2>
Answer:</h2>
![\boxed{x=1, \y=-1, \ z=2}](https://tex.z-dn.net/?f=%5Cboxed%7Bx%3D1%2C%20%5Cy%3D-1%2C%20%5C%20z%3D2%7D)
<h2>
Step-by-step explanation:</h2>
We will use the Gaussian elimination method to solve this problem. To do so, let's follow the following steps:
Step 1: Let's multiply first equation by −2. Next, add the result to the second equation. So:
![\begin{array}{ cccc }~~ x&+~~2~ y&-~~~~~ z&~=~-3\\&-~~~5~ y&+~~3~ z&~=~11\\~~ x&-~~~~~ y&+~~~~ z&~=~4\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7B%20cccc%20%7D~~%20x%26%2B~~2~%20y%26-~~~~~%20z%26~%3D~-3%5C%5C%26-~~~5~%20y%26%2B~~3~%20z%26~%3D~11%5C%5C~~%20x%26-~~~~~%20y%26%2B~~~~%20z%26~%3D~4%5Cend%7Barray%7D)
Step 2: Let's multiply first equation by −1. Next, add the result to the third equation. Thus:
![\begin{array}{ cccc }~~ x&+~~2~ y&-~~~~~ z&~=~-3\\&-~~~5~ y&+~~3~ z&~=~11\\&-~~~3~ y&+~~2~ z&~=~7\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7B%20cccc%20%7D~~%20x%26%2B~~2~%20y%26-~~~~~%20z%26~%3D~-3%5C%5C%26-~~~5~%20y%26%2B~~3~%20z%26~%3D~11%5C%5C%26-~~~3~%20y%26%2B~~2~%20z%26~%3D~7%5Cend%7Barray%7D)
Step 3: Let's multiply second equation by −35, Next, add the result to the third equation. Therefore:
![\begin{array}{ cccc }~~ x&+~~2~ y&-~~~~~ z&~=~-3\\&-~~~5~ y&+~~3~ z&~=~11\\&&+~~\frac{ 1 }{ 5 }~ z&~=~\frac{ 2 }{ 5 }\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7B%20cccc%20%7D~~%20x%26%2B~~2~%20y%26-~~~~~%20z%26~%3D~-3%5C%5C%26-~~~5~%20y%26%2B~~3~%20z%26~%3D~11%5C%5C%26%26%2B~~%5Cfrac%7B%201%20%7D%7B%205%20%7D~%20z%26~%3D~%5Cfrac%7B%202%20%7D%7B%205%20%7D%5Cend%7Barray%7D)
Step 4: solve for z, then for y, then for x:
![\frac{ 1 }{ 5 } ~ z & = \frac{ 2 }{ 5 } \\ \\ \boxed{z & = 2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%201%20%7D%7B%205%20%7D%20~%20z%20%26%20%3D%20%5Cfrac%7B%202%20%7D%7B%205%20%7D%20%5C%5C%20%5C%5C%20%5Cboxed%7Bz%20%26%20%3D%202%7D)
![-5y+3z &= 11\\-5y+3\cdot 2 &= 11\\ \\ \boxed{y &= -1}](https://tex.z-dn.net/?f=-5y%2B3z%20%26%3D%2011%5C%5C-5y%2B3%5Ccdot%202%20%26%3D%2011%5C%5C%20%5C%5C%20%5Cboxed%7By%20%26%3D%20-1%7D)
By substituting
into the first equation, we get the
. So:
![x+2(-1)-2=-3 \\ \\ x-2-2=-3 \\ \\ \boxed{x=1}](https://tex.z-dn.net/?f=x%2B2%28-1%29-2%3D-3%20%5C%5C%20%5C%5C%20x-2-2%3D-3%20%5C%5C%20%5C%5C%20%5Cboxed%7Bx%3D1%7D)